Patients' Experience of Communication During Their Course of Treatment in an Oncology Outpatient Clinic: Qualitative Study. Issue 1 (January 2022) - Prip, Anne; Pii, Kathrine H.; Nielsen, Dorte Lisbet; Jarden, Mary
Abstract : Background: Communication between patients and healthcare professionals becomes increasingly important as patients with cancer are primarily treated in outpatient settings, where the time to communicate is brief. There is a need to understand patients' experiences of communication to ensure person-centered communication during treatment. Objective: The aim of this study was to explore how patients experience communication with healthcare professionals during their course of treatment in an oncology outpatient clinic to elucidate how their needs for support are met. Methods: Data were generated through semistructured qualitative interviews in patients with cancer who received treatment in an oncology outpatient clinic (n = 18). Interpretive description methodology and symbolic interactionism inspired the analytical approach. Results: Three overarching communication categories were generated, namely, verbal practices, relational practices, and nonverbal practices, which reflect distinct characteristics and the quality of the communication. Communication was characterized as being informative, cheerful, and routinized, which the patients found supportive and, contrarily, superficial, task focused, lacking continuity in care, and missing existential dimensions. Conclusion: The communication practice in the oncology outpatient clinic especially supported patients in managing their treatment and side effects. However, psychological, social, and existential concerns were rarely addressed, requiring the patient to self-manage these issues in everyday life while living with cancer. Implications for Practice: Patients are socialized by verbal and nonverbal communication practices in the outpatient clinic, which influences their expectations of what to talk about during their treatment. Methods are needed to support person-centered communication in outpatient settings, so patient care needs are met more broadly.